Leader as coach : restoring employee motivation and performance. (B) - Cates, Karen L., (SAGE Business Cases., 2019)
Kiera, a young, enthusiastic sales rep, was recently promoted to manager of a sales team of five. In her first year on the job, she tackled a major revamp of the company's outdated training materials and organized a regional conference for her area, but neither her boss nor corporate seemed to appreciate the work she had been doing. Without support or guidance from her boss, Kiera was confused. What was she supposed to do? Parts A and B of the case present two different perspectives on coaching. Part B describes how Kiera started to learn the "coach approach" to managing her team with the continued guidance of her executive coach. She learned to apply the same skills that her coach used with her in Part A to diagnose her team, share feedback, and communicate expectations. She was learning how to listen and ask thoughtful questions, but she also needed to expand her awareness to "other-management" and build her own coaching skills to enhance her team's performance.